Mucoactive agents for acute respiratory failure in the critically ill: a systematic review and meta-analysis. Issue 8 (8th June 2020) - Anand, Rohan; McAuley, Daniel F; Blackwood, Bronagh; Yap, Chee; ONeill, Brenda; Connolly, Bronwen; Borthwick, Mark; Shyamsundar, Murali; Warburton, John; Meenen, David van; Paulus, Frederique; Schultz, Marcus J; et al.
Abstract : Purpose: Acute respiratory failure (ARF) is a common cause of admission to intensive care units (ICUs). Mucoactive agents are medications that promote mucus clearance and are frequently administered in patients with ARF, despite a lack of evidence to underpin clinical decision making. The aim of this systematic review was to determine if the use of mucoactive agents in patients with ARF improves clinical outcomes. Methods: We searched electronic and grey literature (January 2020). Two reviewers independently screened, selected, extracted data and quality assessed studies. We included trials of adults receiving ventilatory support for ARF and involving at least one mucoactive agent compared with placebo or standard care. Outcomes included duration of mechanical ventilation. Meta-analysis was undertaken using random-effects modelling and certainty of the evidence was assessed using Grades of Recommendation, Assessment, Development and Evaluation. Results: Thirteen randomised controlled trials were included (1712 patients), investigating four different mucoactive agents. Mucoactive agents showed no effect on duration of mechanical ventilation (seven trials, mean difference (MD) −1.34, 95% CI −2.97 to 0.29, I 2 =82%, very low certainty) or mortality, hospital stay and ventilator-free days. There was an effect on reducing ICU length of stay in the mucoactive agent groups (10 trials, MD −3.22, 95% CI −5.49 to −0.96, I 2 =89%, very low certainty). Conclusion: Our findings do not support the use of mucoactive agents in critically ill patients with ARF. The existing evidence is of low quality. High-quality randomised controlled trials are needed to determine the role of specific mucoactive agents in critically ill patients with ARF. PROSPERO registration number: CRD42018095408.